Environmental context sculpts spatial and temporal visual processing in thalamus - Peelman, Kayla; Haider, Bilal (bioRxiv, 2025)
Behavioral state modulates neural activity throughout the visual system . This is largely due to changes in arousal that alter internal brain state . Much is known about how these internal factors influence visual processing , but comparatively less is known about the role of external environmental contexts . Environmental contexts can promote or prevent certain actions , and it remains unclear if and how this affects visual processing. Here, we addressed this question in the thalamus of awake head-fixed mice while they viewed stimuli but remained stationary in two different environmental contexts: either a cylindrical tube, or a circular running wheel that enabled locomotion. We made silicon probe recordings in the dorsal lateral geniculate nucleus (dLGN) while simultaneously measuring multiple metrics of arousal changes, so that we could control for them across contexts. We found surprising differences in spatial and temporal processing in dLGN across contexts. The wheel context (versus tube) showed elevated baseline activity, and faster but less spatially selective visual responses; however, these visual processing differences disappeared if the wheel no longer enabled locomotion. Our results reveal an unexpected influence of the physical environmental context on fundamental aspects of early visual processing, even in otherwise identical states of alertness and stillness.